EFFECTS OF CORE-PROPRIOCEPTIVE TRAINING ON THE QUALITY OF EXECUTIVE FUNCTIONS IN U13 FEMALE BASKETBALL PLAYERS - Gabriella Makra; Dorottya Bianka Donka; Eszter Panna Torma; Zsuzsa Sükei; László Balogh (University of Debrecen, Institute of Sport Sciences, 2022)
Introduction: Complex scientific work to investigate and develop the factors determining performance is essential to improving sports performance. Creating the neuro-muscular connection is paramount, as it is the cornerstone of movement coordination, and the nervous system is the key to mental components. Objective: Our study aims to demonstrate the positive effects of core-proprioceptive training on executive functions. Method: The DEAC U13 girls' academy basketball players (n=12) participated in a 9-week core-proprioceptive training program. Before and after the program, the players' executive functions were measured with the Vienna Test System. Result: A marked improvement in the measured parameters regarding the evolution of correct and incorrect responses and the reaction time. There is a significant reduction in the number of missed responses. Conclusions: Core-proprioceptive training also improved nerve-muscle connectivity, affecting the quality of executive functions. The results may be implemented in designing training program.